PENGARUH INFORMASI AKUNTANSI DAN NON AKUNTANSI TERHADAP INITIAL RETURN PADA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING DI BURSA EFEK INDONESIA PERIODE 2011â2013 - Febry Anggara Wahyu S, 11.05.52.0190; Aini, Nur (Students Journal of Accounting and Banking, 2015)
This study aims to examine and analyze the effect of accounting and non-accounting information to the initial return on a company doing an initial public offering on the stock exchange Indonesia. The population in this study are all companies listed on the Indonesian Stock Exchange (BEI) 2011-2013. Samples were companies listed on the Indonesian Stock Exchange in the period 2011-2013 in addition to corporate banking and financial services industry. Based on the purposive sampling method, samples obtained 52 companies. This study used multiple linear regression to analyze the data. Based on the results of hypothesis testing, it is known that the level of leverage, earning per share, the amount of the company, the auditors reputation, the reputation of the company underwritter and age did not affect the initial return on a company doing an initial public offering on the Indonesian Stock Exchange. Return on asset positive effect on initial return on a company that does the initial public offering on the Indonesia Stock Exchange.Keywords: Initial Public Offering, The Level of Leverage, Return On Assets, Earnings Per Share Amount of The Company, Auditor Reputation, Reputation Underwritter, The Life of The Company and The Initial Return